Systematic review of physiotherapy interventions to improve gross motor capacity and performance in children and adolescents with an acquired brain injury - Baque, E.; Sakzewski, L.; Barber, L.; Boyd, Roslyn (Informa UK Limited, 2016)
Aim: To systematically review the efficacy of physiotherapy interventions to improve gross motor capacity, performance and societal participation in children aged 5–17 years with an acquired brain injury (ABI). Methods: Randomized and non-randomized controlled trials, cohort, case series, case-control and case studies were included and classified according to grades of evidence. Methodological quality of studies was assessed using the Downs and Black (D&B) scale and quantitative data was analysed using effect sizes. Results: Two home-based studies investigated functional strength training (one ’randomized controlled trial, n = 20, level 2b, D&B = 16/32 and one non-randomized self-control study, n = 19, level 4, D&B = 15/32). Four studies evaluated virtual reality including: one pilot study, n = 50, level 4, D&B = 22/32; one single-subject, non-concurrent, randomized multiple baseline study, n = 3, level 4, D&B = 15/32; one case series study, n = 2, level 4, D&B = 15/32; one case study, n = 1, level 4, D&B = 15/32. Effect sizes for the ’randomized controlled trial ranged between 0.30–1.29 for the Functional Reach and Timed Up and Go outcome measures. Conclusion: There is preliminary evidence to support the efficacy of physiotherapy interventions to improve gross motor outcomes in children with an ABI. Both functional strength training and virtual-reality based therapy are potential treatment options for clinicians to prescribe in either home or clinical settings.